Nano Y-type molecular sieve with high silica-alumina ratio and preparation method thereof

By directly preparing the high-silicon-aluminum nano-Y-type molecular sieve, the problems of cumbersome post-treatment method of high-silicon-aluminum nano-Y-type molecular sieve in the prior art were solved, and the preparation of nano-Y-type molecular sieve with high-silicon-aluminum ratio and uniform particle size was realized.

CN119528170AActive Publication Date: 2025-02-28JILIN UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411725694.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

In the prior art, the post-treatment process of high-silicon Y-type molecular sieve is complicated, has a large pollution, and is prone to cause skeleton defects.

Method used

The high-silicon-aluminum nano-Y-type molecular sieve was prepared by direct method. By mixing water, template agent, aluminum source, silicon source, alkali source and Y-type molecular sieve seed crystals, forming an initial gel, and aging and hydrothermal crystallization, a nano-Y-type molecular sieve with high-silicon-aluminum ratio was obtained.

Benefits of technology

The advantages of high silicon-aluminum ratio, small particle size, uniform particle size, and high crystallinity are achieved, avoiding the cumbersome process and skeleton defects of the post-treatment method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528170A_ABST
    Figure CN119528170A_ABST
Patent Text Reader

Abstract

The invention provides a nano Y-type molecular sieve with a high silica-alumina ratio and a preparation method thereof, and relates to the technical field of molecular sieves. The preparation method comprises the following steps: mixing a silicon source, an aluminum source, an alkali source, water, a Y-type molecular sieve seed crystal and a specific template agent to obtain initial gel, aging the initial gel, and carrying out hydrothermal crystallization on the initial gel to successfully prepare the nano Y-type molecular sieve with a silicon-aluminum ratio (Si / Al) of 6-15. According to the method, a direct method (namely a one-pot method) is adopted, namely, the molecular sieve product with the high silica-alumina ratio is directly synthesized by changing the composition of the initial gel, compared with a post-treatment method, the process is simple, and the defect that the post-treatment method easily causes skeleton defects of the high-silicon Y-type molecular sieve is overcome. The Y-type molecular sieve prepared by the invention has the advantages of high silica-alumina ratio, small particle size, uniform particle size, high crystallization degree and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of molecular sieves, and in particular to a high silicon-aluminum ratio nano Y-type molecular sieve and a preparation method thereof. Background Art

[0002] Molecular sieves are crystalline aluminosilicates with uniform pore structures and are widely used in adsorption, separation and heterogeneous catalysis. Y-type molecular sieve (FAU) is one of the most important members of the zeolite family. It has a three-dimensional 12-membered annular channel system and is a commonly used catalyst material in the field of petroleum fluid catalytic cracking (FCC). Small-sized zeolites play an important role in catalytic and adsorption applications, and smaller zeolite crystals will have a larger surface area and less diffusion restrictions. Y-type molecular sieves with a high silicon-aluminum ratio have the advantages of high catalytic activity, good stability, and resistance to high temperature and high pressure. Compared with traditional Y-type molecular sieves, high silicon-aluminum ratio nano Y-type molecular sieves have a larger specific surface area, can provide more adsorption sites and catalytic active sites, thereby enhancing adsorption and catalytic performance.

[0003] At present, most of the high-silicon Y-type molecular sieves used in industry are obtained by post-processing, mainly by dealuminizing the molecular sieve to obtain a molecular sieve with a high silicon-aluminum ratio. For example, Chinese patent CN114988428B discloses a method for obtaining a high-silicon Y-type molecular sieve by post-processing, which is to dealuminate the industrial finished product NaY zeolite with nitrogen-silicon tetrachloride mixed gas and then pickle it to obtain a Y-type molecular sieve with a high silicon-aluminum ratio (Si / Al=5~35). The post-processing method has the disadvantages of complicated process and high pollution, and this method is easy to cause skeleton defects in the high-silicon Y-type molecular sieve. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a high silicon-aluminum ratio nano Y-type molecular sieve and a preparation method thereof. The present invention adopts a direct method to prepare the Y-type molecular sieve, which has a simple process, and the obtained Y-type molecular sieve has a high silicon-aluminum ratio and a small particle size.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a high silicon-aluminum ratio nano Y-type molecular sieve, comprising the following steps:

[0007] Mix water, a template, an aluminum source, a silicon source, an alkali source and a Y-type molecular sieve seed to obtain an initial gel; the template comprises a first template, a second template and a third template, the first template is one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide and tetrapropylammonium hydroxide, the second template is tetrabutylammonium hydroxide, and the third template is hexadecyltrimethylammonium bromide; the alkali source contains an alkali metal element; the silicon source, the aluminum source and the alkali source are calculated as silicon dioxide, aluminum oxide and alkali metal oxide respectively, and the molar ratio of the first template, the second template, the third template, the silicon source, the aluminum source, the alkali source and water in the initial gel is (0.1-1):(0.5-8):(0.1-1):10:(0.05-1):(0.1-2):(100-500);

[0008] The initial gel is subjected to aging and hydrothermal crystallization in sequence to obtain a high silicon-aluminum ratio nano Y-type molecular sieve.

[0009] Preferably, the aluminum source includes one or more of sodium metaaluminate, pseudo-boehmite, aluminum hydroxide, aluminum chloride, aluminum nitrate, aluminum sulfate and aluminum isopropoxide.

[0010] Preferably, the silicon source includes one or more of sodium silicate, white carbon black, water glass, silica sol and tetraethyl orthosilicate.

[0011] Preferably, the alkali source includes one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide and sodium aluminate.

[0012] Preferably, the molar ratio of the first template, the second template, the third template, the silicon source, the aluminum source, the alkali source and water in the initial gel is (0.1-0.5):(3-6):(0.1-0.4):10:(0.1-0.6):(0.1-0.5):(150-350).

[0013] Preferably, the mass of the Y-type molecular sieve seed crystal is 1-15% of the mass of the silicon source, where the mass of the silicon source is calculated as silicon dioxide.

[0014] Preferably, the aging temperature is room temperature and the aging time is 8 to 96 hours.

[0015] Preferably, the hydrothermal crystallization temperature is 80-180° C. and the time is 12-240 hours.

[0016] Preferably, the hydrothermal crystallization is static crystallization or dynamic crystallization.

[0017] The present invention provides a high silicon-aluminum ratio nano Y-type molecular sieve prepared by the preparation method described in the above technical solution. The silicon-aluminum molar ratio of the high silicon-aluminum ratio nano Y-type molecular sieve is 6-15, and the particle size is 50-100nm.

[0018] The present invention provides a method for preparing a high silicon-aluminum ratio nano Y-type molecular sieve. The present invention mixes a silicon source, an aluminum source, an alkali source, water, a Y-type molecular sieve seed and a specific template agent to obtain an initial gel. After aging, the initial gel is hydrothermally crystallized to successfully prepare a nano Y-type molecular sieve with a silicon-aluminum ratio (Si / Al) of 6 to 15. The present invention adopts a direct method (i.e., a one-pot method), that is, by changing the composition of the initial gel, a molecular sieve product with a high silicon-aluminum ratio is directly synthesized. Compared with the post-treatment method, the process is simple, and the disadvantage that the post-treatment method easily causes the high silicon Y-type molecular sieve to have skeleton defects is avoided. The Y-type molecular sieve prepared by the present invention has the advantages of high silicon-aluminum ratio, small particle size, uniform particle size, and high crystallinity. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 X-ray diffraction patterns of products Y1 to Y12 in the embodiments and comparative examples;

[0020] Figure 2 This is the SEM image of product Y1;

[0021] Figure 3 This is the SEM image of product Y2;

[0022] Figure 4 This is the scanning electron microscope image of product Y3;

[0023] Figure 5 This is the scanning electron microscope image of product Y12. DETAILED DESCRIPTION

[0024] The present invention provides a method for preparing a high silicon-aluminum ratio nano Y-type molecular sieve, comprising the following steps:

[0025] Mix water, a template, an aluminum source, a silicon source, an alkali source and a Y-type molecular sieve seed to obtain an initial gel; the template comprises a first template, a second template and a third template, the first template is one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide and tetrapropylammonium hydroxide, the second template is tetrabutylammonium hydroxide, and the third template is hexadecyltrimethylammonium bromide; the alkali source contains an alkali metal element; the silicon source, the aluminum source and the alkali source are calculated as silicon dioxide, aluminum oxide and alkali metal oxide respectively, and the molar ratio of the first template, the second template, the third template, the silicon source, the aluminum source, the alkali source and water in the initial gel is (0.1-1):(0.5-8):(0.1-1):10:(0.05-1):(0.1-2):(100-500);

[0026] The initial gel is subjected to aging and hydrothermal crystallization in sequence to obtain a high silicon-aluminum ratio nano Y-type molecular sieve.

[0027] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.

[0028] The invention mixes water, a template agent, an aluminum source, a silicon source, an alkali source and a Y-type molecular sieve seed to obtain an initial gel.

[0029] In the present invention, the template includes a first template, a second template and a third template. In the present invention, the first template is one or more of tetramethylammonium hydroxide (TMAOH), tetraethylammonium hydroxide (TEAOH) and tetrapropylammonium hydroxide (TPAOH), preferably tetramethylammonium hydroxide; the tetramethylammonium hydroxide, tetraethylammonium hydroxide and tetrapropylammonium hydroxide are preferably added in the form of aqueous solution, wherein the mass fraction of the tetramethylammonium hydroxide aqueous solution is preferably 25% or 40%, the mass fraction of the tetraethylammonium hydroxide aqueous solution is preferably 25% or 35%, and the mass fraction of the tetrapropylammonium hydroxide aqueous solution is preferably 25% or 40%. In the present invention, the second template is tetrabutylammonium hydroxide (TBAOH), and the tetrabutylammonium hydroxide is preferably added in the form of a tetrabutylammonium hydroxide aqueous solution, and the mass fraction of the tetrabutylammonium hydroxide aqueous solution is preferably 25% or 40%. In the present invention, the third template is hexadecyltrimethylammonium bromide (CTAB).

[0030] In the present invention, the water is preferably deionized water. In the present invention, the aluminum source preferably includes one or more of sodium aluminate, pseudo-boehmite, aluminum hydroxide, aluminum chloride, aluminum nitrate, aluminum sulfate and aluminum isopropoxide, and more preferably sodium aluminate. In the present invention, the silicon source preferably includes one or more of sodium silicate, white carbon black, water glass, silica sol and tetraethyl orthosilicate (TEOS), and more preferably silica sol. In an embodiment of the present invention, the mass content of silicon dioxide (SiO2) in the silica sol is 30-40%. In the present invention, the alkali source contains alkali metal elements, and the alkali source preferably includes one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide and sodium aluminate, wherein sodium aluminate can be used as an aluminum source and an alkali source at the same time. The present invention has no special requirements for the Y-type molecular sieve seed crystals, and is prepared using commercial products in the art or a preparation method well known to those skilled in the art. In an embodiment of the present invention, the silicon-aluminum molar ratio (Si / Al) of the Y-type molecular sieve seed crystals is 50.

[0031] In the present invention, the mixing is preferably carried out by stirring and mixing in a closed environment at room temperature. The present invention has no special requirements on the stirring conditions of the stirring and mixing, and it suffices to mix the components uniformly.

[0032] In the present invention, the silicon source, aluminum source and alkali source are calculated as silicon dioxide, aluminum oxide and alkali metal oxide respectively, and the molar ratio of the first template, the second template, the third template, the silicon source, the aluminum source, the alkali source and water in the initial gel is (0.1-1):(0.5-8):(0.1-1):10:(0.05-1):(0.1-2):(100-500) (expressed as R1:R2:R3:SiO2:Al2O3:M2O:H2 O=(0.1~1):(0.5~8):(0.1~1):10:(0.05~1):(0.1~2):(100~500), wherein R1, R2 and R3 represent the first template, the second template and the third template respectively, and M2O is an alkali metal oxide), preferably (0.1~0.5):(3~6):(0.1~0.4):10:(0.1~0.6):(0.1~0.5):(150~350). In the present invention, the mass of the Y-type molecular sieve seed is preferably 1~15% of the mass of the silicon source, more preferably 5~10%, and the mass of the silicon source is calculated as silicon dioxide.

[0033] After obtaining the initial gel, the present invention sequentially performs aging and hydrothermal crystallization on the initial gel to obtain a high silicon-aluminum ratio nano Y-type molecular sieve.

[0034] In the present invention, the aging temperature is preferably room temperature, and the aging time is preferably 8 to 96 hours, and can be 24 hours, 48 ​​hours, 60 hours or 72 hours. The present invention makes the components in the gel more evenly mixed through the aging, and the molecular sieve slowly nucleates during the aging process, shortening the growth cycle of the molecular sieve.

[0035] In the present invention, the temperature of the hydrothermal crystallization is preferably 80 to 180°C, more preferably 120 to 140°C, and the time is preferably 12 to 240 hours, more preferably 72 to 120 hours. In the present invention, the aging liquid obtained by the aging is preferably charged into a reactor with a polytetrafluoroethylene lining and placed in an oven for the hydrothermal crystallization. In the present invention, the hydrothermal crystallization is preferably static crystallization or dynamic crystallization, and the dynamic crystallization is preferably carried out under rotating conditions.

[0036] After the hydrothermal crystallization is completed, the present invention preferably sequentially performs solid-liquid separation, solid phase washing and drying on the obtained crystallization reaction liquid to obtain the high silicon-aluminum ratio nano Y-type molecular sieve. In the present invention, the solid-liquid separation method is preferably centrifugation, and the washing is preferably water washing.

[0037] The present invention adopts a seeding method and a specific template agent to synthesize a high silicon-aluminum ratio nano Y-type molecular sieve in a one-pot method (direct method). The seeding method can shorten the induction period in the formation process of the molecular sieve, accelerate crystallization, and inhibit the impurity phase. The direct method for synthesizing Y molecular sieve has the advantages of simple operation, uniform aluminum distribution, and stable skeleton, and is an ideal method for preparing a high silicon-aluminum ratio nano Y-type molecular sieve. The present invention successfully synthesizes a nano Y-type molecular sieve with a high silicon-aluminum ratio and a high degree of crystallization.

[0038] The present invention provides a high silicon-aluminum ratio nano Y-type molecular sieve prepared by the preparation method described in the above technical solution, wherein the silicon-aluminum molar ratio (Si / Al) of the high silicon-aluminum ratio nano Y-type molecular sieve is 6 to 15, preferably 8 to 12, more preferably 10 to 11.2, and the particle size is 50 to 100 nm.

[0039] In order to further illustrate the present invention, the high silicon-aluminum ratio nano Y-type molecular sieve and its preparation method provided by the present invention are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.

[0040] In each example, the Y-type molecular sieve seed crystals were purchased from Tosoh Corporation of Japan, model HSZ-385HUA (molar ratio SiO2 / Al2O3=100).

[0041] Example 1

[0042] The preparation method of high silicon-aluminum ratio nano Y-type molecular sieve is as follows:

[0043] 0.05 g of sodium aluminate (containing 41 wt% Na2O and 48 wt% Al2O3), 3.75 g of silica sol (SiO2 content 40 wt%), 2.09 g of deionized water, 0.13 g of 25 wt% tetramethylammonium hydroxide aqueous solution, 9.10 g of 40 wt% tetrabutylammonium hydroxide aqueous solution, 0.09 g of hexadecyltrimethylammonium bromide and 0.08 g of Y-type molecular sieve seed crystals were added to a reaction vessel, and stirred evenly under closed and room temperature conditions to obtain a reaction solution (i.e., initial gel); the reaction solution was aged at room temperature for 24 h, and then the reaction solution was charged into a reactor with a polytetrafluoroethylene liner and statically crystallized in an oven at 140°C for 3 days.

[0044] After the hydrothermal reaction was completed, a centrifugal device was used to separate the solid and the liquid. The solid product was washed with water and dried in an oven at 90° C. for 8 hours to obtain a Y-type molecular sieve product, which was recorded as product Y1.

[0045] The silicon-to-aluminum ratio (Si / Al molar ratio) of product Y1 was determined and listed in Table 1. The silicon-to-aluminum ratio (Si / Al) of product Y1 was calculated by inductively coupled plasma emission spectroscopy (ICP) data, and the calculation method was a conventional technical method in the art.

[0046] Figure 1 The middle curve Y1 is the X-ray diffraction pattern of product Y1. By comparing it with the standard diffraction pattern published by the International Zeolite Association, it can be seen that product Y1 is a molecular sieve with a FAU structure, and the sample XRD is highly close to the standard spectrum, with a straight baseline without bulges, indicating a high degree of crystallinity. Figure 2 This is the scanning electron microscope image of product Y1. The particle size is between 80 and 100 nm, and the particle size is uniform.

[0047] Example 2

[0048] The preparation method of high silicon-aluminum ratio nano Y-type molecular sieve is as follows:

[0049] 0.08 g of sodium aluminate (containing 41 wt% Na2O and 48 wt% Al2O3), 3.75 g of silica sol (SiO2 content 40 wt%), 4.42 g of deionized water, 0.11 g of 25 wt% tetramethylammonium hydroxide aqueous solution, 8.27 g of 40 wt% tetrabutylammonium hydroxide aqueous solution, 0.09 g of hexadecyltrimethylammonium bromide and 0.1 g of Y-type molecular sieve seed crystals were added to a reaction vessel, and stirred evenly under closed and room temperature conditions to obtain a reaction solution; the reaction solution was aged at room temperature for 48 h, and then the reaction solution was charged into a reactor with a polytetrafluoroethylene liner and statically crystallized in an oven at 120°C for 5 days.

[0050] After the hydrothermal reaction was completed, a centrifugal device was used to separate the solid and the liquid. The solid product was washed with water and dried in an oven at 90° C. for 8 hours to obtain a Y-type molecular sieve product, which was recorded as product Y2.

[0051] The silicon-to-aluminum ratio (Si / Al) of product Y2 was measured and listed in Table 1. The silicon-to-aluminum ratio (Si / Al) of product Y2 was calculated by inductively coupled plasma emission spectroscopy (ICP) data, and the calculation method was a conventional technical method in the art.

[0052] Figure 1 The middle curve Y2 is the X-ray diffraction pattern of product Y2. By comparing it with the standard diffraction pattern published by the International Zeolite Association, it can be seen that product Y2 is a molecular sieve with a FAU structure. Figure 3 This is the scanning electron microscope image of product Y2. The particle size is between 50 and 100 nm and the particle size is uniform.

[0053] Example 3

[0054] The preparation method of high silicon-aluminum ratio nano Y-type molecular sieve is as follows:

[0055] 0.06 g of sodium aluminate (containing 41 wt% Na2O and 48 wt% Al2O3), 3.75 g of silica sol (SiO2 content 40 wt%), 3.00 g of deionized water, 0.14 g of 25 wt% tetramethylammonium hydroxide aqueous solution, 6.49 g of 40 wt% tetrabutylammonium hydroxide aqueous solution, 0.09 g of hexadecyltrimethylammonium bromide and 0.15 g of Y-type molecular sieve seed crystals were added to a reaction vessel, and stirred evenly under closed and room temperature conditions to obtain a reaction solution; the reaction solution was aged at room temperature for 60 h, and then the reaction solution was charged into a reactor with a polytetrafluoroethylene liner and statically crystallized in an oven at 140°C for 3 days.

[0056] After the hydrothermal reaction was completed, a centrifugal device was used to separate the solid and the liquid. The solid product was washed with water and dried in an oven at 90° C. for 8 hours to obtain a Y-type molecular sieve product, which was recorded as product Y3.

[0057] The silicon-to-aluminum ratio (Si / Al) of product Y3 was measured and listed in Table 1. The silicon-to-aluminum ratio (Si / Al) of product Y3 was calculated by inductively coupled plasma emission spectroscopy (ICP) data, and the calculation method was a conventional technical method in the art.

[0058] Figure 1 The middle curve Y3 is the X-ray diffraction pattern of product Y3. By comparing it with the standard diffraction pattern published by the International Zeolite Association, it can be seen that product Y3 is a molecular sieve with a FAU structure. Figure 4 This is a scanning electron microscope image of product Y3. The particle size is between 50 and 100 nm and the particle size is uniform.

[0059] Example 4

[0060] Compared with Example 1, 5.00 g of silica sol (SiO2 content 30 wt%) and 0.84 g of deionized water were added in Example 4, and the remaining schemes and conditions were the same as those in Example 1, to prepare a Y-type molecular sieve product, which was recorded as product Y5.

[0061] Figure 1 The middle curve Y5 is the X-ray diffraction pattern of product Y5. By comparing with the standard diffraction pattern published by the International Zeolite Association, it can be seen that product Y5 is a molecular sieve with a FAU structure. The silicon-to-aluminum ratio (Si / Al) of product Y5 was measured and listed in Table 1. Among them, the silicon-to-aluminum ratio (Si / Al) of product Y5 was calculated by inductively coupled plasma emission spectroscopy (ICP) data, and the calculation method is a conventional technical method in the field.

[0062] Example 5

[0063] Compared with Example 2, the aging time in Example 5 is 72 hours, and the other schemes and conditions are the same as those in Example 2, and a Y-type molecular sieve product is prepared, which is recorded as product Y6.

[0064] Figure 1 The middle curve Y6 is the X-ray diffraction pattern of product Y6. By comparing with the standard diffraction pattern published by the International Zeolite Association, it can be seen that product Y6 is a molecular sieve with a FAU structure. The silicon-to-aluminum ratio (Si / Al) of product Y6 was measured and listed in Table 1. Among them, the silicon-to-aluminum ratio (Si / Al) of product Y6 was calculated by inductively coupled plasma emission spectroscopy (ICP) data, and the calculation method is a conventional technical method in the field.

[0065] Example 6

[0066] Compared with Example 3, Example 6 adopts dynamic crystallization (rotation speed is 50 rpm), and the other schemes and conditions are the same as those of Example 3, and a Y-type molecular sieve product is prepared, which is recorded as product Y7.

[0067] Figure 1 The middle curve Y7 is the X-ray diffraction pattern of product Y7. By comparing with the standard diffraction pattern published by the International Zeolite Association, it can be seen that product Y7 is a molecular sieve with a FAU structure. The silicon-aluminum ratio (Si / Al) of product Y7 was measured and listed in Table 1. Among them, the silicon-aluminum ratio (Si / Al) of product Y7 was calculated by inductively coupled plasma emission spectroscopy (ICP) data, and the calculation method is a conventional technical method in the field.

[0068] Comparative Example 1

[0069] The NaY molecular sieve synthesized by traditional methods (purchased from Luoyang Jianlong Micro-Nano New Materials Co., Ltd.) was ground into powder, dispersed in deionized water, stirred for 2 hours, and then separated into solid and liquid using a centrifuge. The solid product was dried in an oven at 90°C for 8 hours to obtain a comparative product, recorded as product Y4.

[0070] Figure 1 Curve Y4 in the middle is the X-ray diffraction pattern of product Y4. By comparing it with the standard diffraction pattern published by the International Zeolite Association, it can be seen that product Y4 is a molecular sieve with a FAU structure. The silicon-aluminum ratio (Si / Al) of product Y4 was measured and listed in Table 1. Among them, the silicon-aluminum ratio (Si / Al) of product Y4 was calculated by inductively coupled plasma emission spectroscopy (ICP) data, and the calculation method is a conventional technical method in the field.

[0071] Comparative Example 2

[0072] Compared with Example 1, the crystallization temperature in Comparative Example 2 is 200° C., and the remaining schemes and conditions are the same as those in Example 1, and a comparative product is prepared, which is recorded as product Y8.

[0073] Figure 1 The middle curve Y8 is the X-ray diffraction pattern of product Y8. By comparing it with the standard diffraction pattern published by the International Zeolite Association, it can be seen that product Y8 is not a Y-type molecular sieve.

[0074] Comparative Example 3

[0075] Compared with Example 1, no Y-type molecular sieve seed crystals were added in Comparative Example 3, and the remaining schemes and conditions were the same as those in Example 1, to prepare a comparative product, which was recorded as product Y9.

[0076] Figure 1 The middle curve Y9 is the X-ray diffraction pattern of product Y9. By comparing it with the standard diffraction pattern published by the International Zeolite Association, it can be seen that product Y9 is not a Y-type molecular sieve.

[0077] Comparative Example 4

[0078] Compared with Example 1, in Comparative Example 4, no 40 wt % tetrabutylammonium hydroxide aqueous solution was added, and the remaining schemes and conditions were the same as those in Example 1, to prepare a comparative product, which was recorded as product Y10.

[0079] Figure 1 The middle curve Y10 is the X-ray diffraction pattern of product Y10. By comparing it with the standard diffraction pattern published by the International Zeolite Association, it can be seen that product Y10 is not a Y-type molecular sieve.

[0080] Comparative Example 5

[0081] Compared with Example 1, in Comparative Example 5, no 25 wt % tetramethylammonium hydroxide aqueous solution was added, and the remaining schemes and conditions were the same as those in Example 1, to prepare a comparative product, which was recorded as product Y11.

[0082] Figure 1 The middle curve Y11 is the X-ray diffraction pattern of product Y11. By comparing it with the standard diffraction pattern published by the International Zeolite Association, it can be seen that product Y11 is a molecular sieve with poor crystallinity and FAU structure, and has no use value.

[0083] Comparative Example 6

[0084] Compared with Example 1, no hexadecyltrimethylammonium bromide was added in Comparative Example 6, and the remaining schemes and conditions were the same as those in Example 1, to prepare a comparative product, which was recorded as product Y12.

[0085] Figure 1 The middle curve Y12 is the X-ray diffraction pattern of product Y12. By comparing it with the standard diffraction pattern published by the International Zeolite Association, it can be seen that product Y12 is a molecular sieve with a FAU structure. Figure 5 The scanning electron microscope image of product Y12 shows that the particle size is uneven and relatively large. The silicon-to-aluminum ratio (Si / Al) of product Y12 is measured and listed in Table 1. The silicon-to-aluminum ratio (Si / Al) of product Y12 is calculated by inductively coupled plasma emission spectroscopy (ICP) data, and the calculation method is a conventional technical method in the art.

[0086] Table 1 Silicon to aluminum ratio (Si / Al) of products Y1 to Y7 and Y12

[0087] product Y1 Y2 Y3 Y4 Y5 Y6 Y7 Y12 Si / Al 11.2 8.6 9.6 2.4 10.9 8.3 9.4 10.8

[0088] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a high silicon-aluminum ratio nano Y-type molecular sieve, characterized in that: The following steps are involved: Mix water, a template, an aluminum source, a silicon source, an alkali source and a Y-type molecular sieve seed to obtain an initial gel; the template comprises a first template, a second template and a third template, the first template is one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide and tetrapropylammonium hydroxide, the second template is tetrabutylammonium hydroxide, and the third template is hexadecyltrimethylammonium bromide; the alkali source contains an alkali metal element; the silicon source, the aluminum source and the alkali source are calculated as silicon dioxide, aluminum oxide and alkali metal oxide respectively, and the molar ratio of the first template, the second template, the third template, the silicon source, the aluminum source, the alkali source and water in the initial gel is (0.1-1):(0.5-8):(0.1-1):10:(0.05-1):(0.1-2):(100-500); The initial gel is subjected to aging and hydrothermal crystallization in sequence to obtain a high silicon-aluminum ratio nano Y-type molecular sieve.

2. The preparation method according to claim 1, characterized in that: The aluminum source includes one or more of sodium metaaluminate, pseudo-boehmite, aluminum hydroxide, aluminum chloride, aluminum nitrate, aluminum sulfate and aluminum isopropoxide.

3. The preparation method according to claim 1, characterized in that: The silicon source includes one or more of sodium silicate, white carbon black, water glass, silica sol and tetraethyl orthosilicate.

4. The preparation method according to claim 1, characterized in that: The alkali source includes one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide and sodium aluminate.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The molar ratio of the first template, the second template, the third template, the silicon source, the aluminum source, the alkali source and water in the initial gel is (0.1-0.5):(3-6):(0.1-0.4):10:(0.1-0.6):(0.1-0.5):(150-350).

6. The preparation method according to claim 1 or 3, characterized in that: The mass of the Y-type molecular sieve seed crystal is 1-15% of the mass of the silicon source, where the mass of the silicon source is calculated as silicon dioxide.

7. The preparation method according to claim 1, characterized in that: The aging temperature is room temperature and the aging time is 8 to 96 hours.

8. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal crystallization is 80-180° C., and the time is 12-240 hours.

9. The preparation method according to claim 8, characterized in that: The hydrothermal crystallization is static crystallization or dynamic crystallization.

10. The high silicon-aluminum ratio nano Y-type molecular sieve prepared by the preparation method according to any one of claims 1 to 9, wherein the silicon-aluminum molar ratio of the high silicon-aluminum ratio nano Y-type molecular sieve is 6 to 15 and the particle size is 50 to 100 nm.

Citation Information

Patent Citations

  • A high silica-to-alumina ratio Y-type molecular sieve, its preparation method and application

    CN114988428B

  • Preparation method of high-silica-alumina-ratio Y-type molecular sieve

    CN110963502A

  • Metal-modified hierarchical-pore high-silicon Y molecular sieve as well as preparation method and application thereof

    CN116262623A

  • Preparation method of Y-type molecular sieve

    CN118724011A

  • A bi-microporous / mesoporous composite molecular sieve and preparation process thereof

    SG180418A1